Inspired by Soldier Bees: A Defense Mechanism for Detecting Impersonated Sensor Nodes in Wireless Sensor Networks (International Journal of Food and Nutritional Sciences, 2021)
Through the utilization of this mechanism, we can promptly notify the base station of any potentially malicious nodes within the network and continuously monitor their positional changes. In response to these security concerns, we have developed an advanced secure Artificial Bee Colony Optimizer algorithm, enriched with swarm intelligence. This algorithm facilitates comprehensive exploration of multiple data transmission paths from sensors to sink nodes, particularly when dealing with scenarios involving potential malicious nodes. In order to establish secure communication among nodes, we have seamlessly integrated the Elliptic Curve Digital Signature Algorithm (ECDSA) into our framework. This integration offers several key advantages, including the rapid identification of compromised nodes, a reduction in authentication delays, and the minimization of packet loss. The core strengths of our algorithm encompass swift detection and isolation of compromised nodes, resulting in improved overall network security. Importantly, this process is executed without causing harm to the other nodes in the network. As a result, our scheme significantly enhances energy efficiency, boosts packet delivery ratios, and maximizes throughput within the Wireless Sensor Network (WSN).